2020
DOI: 10.3390/math8111862
|View full text |Cite
|
Sign up to set email alerts
|

Transitivity in Fuzzy Hyperspaces

Abstract: Given a metric space (X,d), we deal with a classical problem in the theory of hyperspaces: how some important dynamical properties (namely, weakly mixing, transitivity and point-transitivity) between a discrete dynamical system f:(X,d)→(X,d) and its natural extension to the hyperspace are related. In this context, we consider the Zadeh’s extension f^ of f to F(X), the family of all normal fuzzy sets on X, i.e., the hyperspace F(X) of all upper semicontinuous fuzzy sets on X with compact supports and non-empty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…The main results in this section are the equivalence between the Devaney chaos of f in K(X) and of f in F (X) and, as a consequence, the equivalence of Devaney chaos for a continuous linear operator T on a metrizable and complete locally convex space X, for its Zadeh extension T defined on the space of normal fuzzy sets F (X) and for the induced hyperspace map T on K(X). This extends previous results of D. Jardón, I. Sánchez, and M. Sanchis about the transitivity in fuzzy metric spaces [4] (see also [20]) and another result of N. Bernardes, A. Peris, and F. Rodenas [2] about the linear Devaney chaos of locally convex spaces.…”
Section: Periodic Points and Devaney Chaossupporting
confidence: 88%
See 4 more Smart Citations
“…The main results in this section are the equivalence between the Devaney chaos of f in K(X) and of f in F (X) and, as a consequence, the equivalence of Devaney chaos for a continuous linear operator T on a metrizable and complete locally convex space X, for its Zadeh extension T defined on the space of normal fuzzy sets F (X) and for the induced hyperspace map T on K(X). This extends previous results of D. Jardón, I. Sánchez, and M. Sanchis about the transitivity in fuzzy metric spaces [4] (see also [20]) and another result of N. Bernardes, A. Peris, and F. Rodenas [2] about the linear Devaney chaos of locally convex spaces.…”
Section: Periodic Points and Devaney Chaossupporting
confidence: 88%
“…We recall that Banks [21], Liao, Wang, and Zhang [22], and Peris [23] independently characterized the topological transitivity for (K(X), f ) in terms of the weak mixing property for (X, f ). Concerning the space of fuzzy sets, in [4], the authors showed (Theorem 3) the equivalences of the weak mixing property of f on X with the transitivity of f on F ∞ (X) or on F 0 (X). They also considered the fuzzy space F (X) endowed with the sendograph metric and the endograph metric.…”
Section: Periodic Points and Devaney Chaosmentioning
confidence: 99%
See 3 more Smart Citations